Urological and Gynaecological Chronic Pelvic Pain Current Therapies - Moldwin, Robert M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text is designed for those clinicians who feel comfortable diagnosing these illnesses and wish to enhance their knowledge base and skill set regarding treatment options. Referrals for pelvic pain are common in urological and gynaecological practice; and may lead to varied diagnoses such as interstitial cystitis/bladder pain syndrome, chronic prostatitis/chronic pelvic pain syndrome, pelvic floor dysfunction, chronic orchialgia, and vulvodynia. To make matters more complex, each of these conditions is frequently associated by co-morbidities. The text is unique in being organized by the multiple and multifaceted therapies that are available, rather than by specific disorders. The text is richly illustrated with multiple diagrams, figures, and tables, making it the (3z(Bgo to(3y (Band (3z(Bhow to(3y (Breference for patient treatment.s
The Evolution of Therapy for Chronic Pelvic Pain -- The Changing Role of Organized Patient Support for the Chronic Pelvic Pain Patient -- Practical Psychosocial Management of Urologic Chronic Pelvic Pain Syndromes,- Advanced Practice Nursing Care for the Pelvic Pain Patient -- Diet Therapy in the Context of Chronic Pelvic Pain -- The Role of Acupuncture in the management of Chronic Pelvic Pain -- Phytotherapy in Chronic Pelvic Pain -- Management of Interstitial Cystitis/Bladder Pain Syndrome with Tricyclic Antidepressants -- Bladder Surface Mucin Analogues -- Neuroleptic Agents for Chronic Pelvic Pain -- Anti-allergic Compounds in Chronic Pelvic Pain -- Opioids and Related Medications -- Hormonal Therapy for Pelvic Pain -- Non-curgical Management of Vulvar Pain -- Immunomodulators for Interstitial Cystitis/Bladder Pain Syndrome -- Other Oral Agents for Chronic Pelvic Pain -- Nerve Blocks -- Intravesical Therapy for Bladder Pain Syndrome/Interstitial Cystitis: Dimethyl Sulfoxide -- Intravesical Lidocaine in Interstitial Cystitis/Bladder Pain Syndrome -- Innovative Intravesical Therapies -- Endoscopic Procedures for Interstitial Cystitis/Bladder Pain Syndrome -- Botulinum Toxin Endoscopic Injection for Pelvic Pain -- Neuromodulation -- Cystectomy/Supravesical Diversion for Interstitial Cystitis -- Surgery for Vulvovaginal Pain Disorders and Dyspareunia -- The Surgical Management of Scrotal Pain -- Therapy for Interstitial Cystitis/Bladder Pain Syndrome and Other Forms of Pelvic Pain During Pregnancy.
Keywords: Medicine; Urology; Medicine & Public Health; Urology